Coping and Cyberchondria in a Pandemic: A Study on Young Adults - Kathryn Nicole Sam; P Nupur Jain; H B Arpitha; Tanvi Raghuram; Advaith Jaikumar; Rituparna Chakraborty; Santhosh Kareepadath Rajan (Journal of Mental Health and Human Behaviour, 2023)
Background: During the COVID-19 pandemic, there was a significant increase in online health information-seeking (HIS) behavior, leading to increased levels of psychological distress. Objective: This study examines whether proactive, preventive, and avoidance coping styles hinder or promote cyberchondria, anxiety characterized by excessive online HIS behavior during the pandemic. Materials and Methods: The sample included 286 Indian young adults who responded to the Proactive Coping Inventory and Cyberchondria Severity Scale-12. The data were collected after the rapid spread of COVID-19 in India. Results: The correlation analysis revealed that proactive coping had a weak negative relationship with cyberchondria, while avoidance coping had a weak positive relationship. Regression analysis showed proactive coping as an inverse predictor of cyberchondria. Conclusions: This study was one of the few that examined the relationship between coping and cyberchondria during the pandemic. The findings provide a foundation for future research on cyberchondria in collectivistic cultures like India.